Riding the Wind and Cleaving the Waves: Strategic Competitions and Green Coalitions among East Asian Automakers in Thailand’s Electric Vehicle Market - Min Ye Paing HEIN (East Asian Policy)
Thailand has been using generous incentives to power its electric vehicle (EV) market. Chinese brands have entered the scene to capture a significant market share while Korean and Japanese automakers are still jostling for niche market positions. This article examines the dynamics of this green rush across three dimensions: manufacturing capacity, competitive pricing and green coalitions. Despite being driven by incentives and competition, Thailand’s EV market still faces significant challenges in its role as an engine of growth.